2013
DOI: 10.1002/anie.201306825
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Dehydrogenation on Nanocarbon: Identification and Quantification of Active Sites by Chemical Titration

Abstract: Ketonic carbonyl groups are catalytic active sites for oxidative dehydrogenation (ODH) reactions on carbon nanotubes. The quantity of these groups could be calculated from chemical titration with hydrazine compounds. ODH catalytic activity of nanocarbon is directly correlated with surface concentration of ketonic carbonyl groups, and the turnover frequency normalized by the number of active sites reflects the intrinsic activity of nanocarbon catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
209
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 266 publications
(227 citation statements)
references
References 43 publications
17
209
0
1
Order By: Relevance
“…As shown in Figure 1a,t he chemical titration on the oxidized carbon-nanotube (o-CNT) catalysts was performed under steady-state conditions.Phenyl hydrazine (PH) was chosen as the titrant because its molecular size,structure, and polarity are similar to that of EB.T he similarities between the molecules allows PH to be used as an appropriate analogue to quantify the amount of active sites which could possibly be contacted by and react with EB. [14] It has also been proven by independent control experiments that there are no side reactions between the titrant PH and reactants O 2 or EB under the chosen reaction conditions. As shown in Figure 1a,t he EB conversion rate (areal rate) dropped dramatically once the titrant PH has been introduced in situ (Figure 1a,t itration start).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…As shown in Figure 1a,t he chemical titration on the oxidized carbon-nanotube (o-CNT) catalysts was performed under steady-state conditions.Phenyl hydrazine (PH) was chosen as the titrant because its molecular size,structure, and polarity are similar to that of EB.T he similarities between the molecules allows PH to be used as an appropriate analogue to quantify the amount of active sites which could possibly be contacted by and react with EB. [14] It has also been proven by independent control experiments that there are no side reactions between the titrant PH and reactants O 2 or EB under the chosen reaction conditions. As shown in Figure 1a,t he EB conversion rate (areal rate) dropped dramatically once the titrant PH has been introduced in situ (Figure 1a,t itration start).…”
mentioning
confidence: 92%
“…[10][11][12] The chemical titration (passivation) method could provide the surface concentration of major oxygen functionalities on carbon nanotube (CNT) surfaces. [13,14] However,t he ex situ process cannot provide any information on the active sites under steady-state conditions and it also requires as eries of samples and tedious steps,w hich is not practical for kinetic studies.T oconnect the chemical structure and quantity of the active sites to their steady-state intrinsic activity,wepropose here an in situ titration technique as shown in Scheme 1. The direct measurement of the catalytic activity as af unction of titrant consumption provides firm chemical evidence for the identity and quantity of ODH active sites on carbon catalysts.…”
mentioning
confidence: 99%
“…Loh's group performed in situ Fourier transform infrared (FTIR) and electron spin resonance (ESR) spectroscopies to elucidate that the boundary defects (edges and vacancies) of base-treated graphene oxide (ba-GO) can effectively activate oxygen molecules to generate superoxide radicals, whereas the carboxylic groups M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 4 functionalized at the edging defects are capable of synergistically trapping the reactants via the localized unpaired electrons [13]. Besides, chemical titration was adopted as a fantastic strategy to selectively block either ketonic carbonyl (C=O), hydroxyl (-OH), or carboxylic groups (-COOH) on the carbon catalysts to probe the effect of the functional groups on catalytic reactions, and kenotic groups were discovered to account for the intrinsic activity of decomposition of H 2 O 2 and oxidative dehydrogenation (ODH) reactions [14][15][16]. Deng et al…”
Section: Introductionmentioning
confidence: 99%
“…They attributed the reaction to the combined contribution of the high electron conductivity of graphitic surface and the high reaction activity of the zigzag carbon on rGO [24,25]. In addition, research on the mechanism of carbon catalysis suggested that oxygen containing functional groups, especially carbonyl/quinone groups on nanocarbon, which were rich in electrons, may act as the catalytic active sites for oxidative dehydrogenation of alkanes or dye reduction [26,27]. In contrast, Pumera's group raised a different point of view about the catalytic mechanism.…”
Section: Introductionmentioning
confidence: 99%